SISTEM INFORMASI PERENCANAAN BAHAN BAKU MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING STUDI KASUS DI PT. POLIPLAS MAKMUR SANTOSA UNGARAN - Sumeyka Sumeyka (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2019)
Currently the development of information technology is growing rapidly. Therefore the application of information systems in agencies and companies is needed because information technology makes the performance will be implemented well and can handle a variety of data processing. One company that requires information technology is PT. Poliplas Makmur Santosa Ungaran. Inventory system used at PT. Makmur Santosa Ungaran Poliplas is still in the form of notes in the form of spreadsheets that are concurrently daily, making it vulnerable to errors in planning raw material requirements, and the uncontrolled use of production raw materials such as dyes. Therefore we need an adequate raw material planning information system to process data and make raw material planning reports automatically. The purpose of this study is to determine the amount and time of raw materials that must be available for the smooth production process. The problem formulated is when the raw material must be available at PT. Poliplas Makmur Santosa with the right amount and time. The method used in this research is Material Requirement Planning (MRP). The results of this study indicate that the implementation of a computerized system at PT. Poliplas Makmur Santosa Ungaran can support the smooth production related to the availability of the right material, with the right amount and time so that data storage can be more safe and efficient, the program used to make this application uses the VB programming language. NET and SQL Server 2008 as database management.